Association of age and dietary sodium intake in patients with heart failure: testing mediating effects of preference for salt and enjoyment of sodium-restricted diet. (29th July 2021) - Chung, ML; Moser, DK; Miller, JL; Lennie, TA
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): National Institutes of Health (NIH) Background: The poor taste foods in a low sodium diet and patients' preferences for salty foods are known barriers to sodium restricted diet (SRD) adherence. Older adults may experience less enjoyment of SRD due to decreased sense of taste. However, little is known about how age is associated with sodium intake, preference for salt, and enjoyment of SRD in patients with heart failure (HF). Purpose: The purpose of this study was to examine effect of age on dietary sodium intake through their preference for salt and enjoyment of SRD in patients with HF. Methods:  In this cross-sectional study, we used baseline data from participants in a randomized controlled trial of a SRD intervention for patients with HF and their caregivers. Patients were asked to collect 24-hour urine to measure dietary sodium intake. Preference for salty food and enjoyment of SRD were assessed using a question on an 11-point numeric scale (range 0 to 10). Parallel mediation analyses were conducted using the PROCESS macro program in SPSS with 5, 000 bootstrap samples. Results: A total of 136 patients with HF (64% male, mean age = 60.3 ± 14.4, range 27 to 90, 80.1% white) had a mean 24-hr urine sodium of 4320mg (SD = 2053, range: 1553 mg – 11495 mg) with most (71%) having a 24-hr urine sodium > 3000mg. The mean preference for salty food was 5.3 (SD = 2.8) on a scale from 0 to 10 with 10 indicating greater preference and enjoyment of SRD was 4.4 (SD = 2.5) on the same scale. Age was significantly associated with sodium intake in that older patients were more likely to eat less sodium (effect= -40.3236, 95% CI= [-63.7151, -16.9321]). The indirect effects of age on sodium intake through preference of salty food (effect= .7033, 95% CI = [-2.3361, 4.5357]) and enjoyment of SRD (effect = -.0271, 95% CI = [ -3.2736, 2.2213]) were not significant, indicating that these factors did not mediate the relationship between age and dietary sodium consumption. When we controlled gender, education, and ethnicity, age was also associated with sodium intake, but the two indirect effects were not significant. Conclusion: Although most patients consumed foods high in sodium, older patients were more likely to consume foods lower in salt. However, contrary to what we expected, preference for salty foods and enjoyment of SRD did not play mediator roles in the association of age with salt consumption. The findings suggest that older adults may need different types of intervention to promote adherence than younger patients. Further research is needed to explore other factors related to SRD (e.g., efficacy of SRD or perceived control of diet behaviors) that affect sodium intake in patients with HF.